KESEIMBANGAN PEREKONOMIAN PASAR BARANG DAN PASAR UANG DALAM PERSPEKTIF ISLAM - Johan Wahyu Wicaksono (el Hakim Press, 2025)
Equilibrium in the goods and money markets is a key requirement for generating aggregate demand in the macroeconomy. Without equilibrium between these two markets, economic stability is less likely to function effectively. In practice, economic equilibrium is difficult to achieve precisely, even though it can be determined theoretically. This is due to the lag in the implementation of policies, which always adapt to rapid economic changes. Therefore, policymakers can do their best to align the equilibrium points of the goods and money markets as closely as possible with theoretically formulated models based on existing data. The existence of theories and models in determining policy direction and formulation is crucial as a basis for decision-making. With appropriate theories and models, policies will be more focused, measurable, and on-target. One popular theory and model in economics is the IS-LM model. In the IS-LM model, economic equilibrium is the point where the IS curve and the LM curve intersect. This point indicates the interest rate r and income level Y, which satisfy the conditions for equilibrium in both the goods and money markets. In other words, at this intersection, actual expenditure equals planned expenditure, and the demand for real money balances equals supply. The IS-LM model of economic equilibrium continues to generate debate among Islamic economists regarding its relevance for use in Islamic economics. After conducting an analysis, the author concludes that the IS-LM model is not relevant for analyzing equilibrium in the goods and money markets from an Islamic economic perspective. However, if adjusted by replacing the interest rate variable with the expected rate of profit and the dues of idle funds/assets, the IS-LM model becomes more relevant to Islamic economic concepts. This approach creates a new equilibrium model for the goods and money markets in accordance with Islamic concepts. An increase in the expected rate of profit and dues of idle funds/assets will encourage increased investment and optimize the use of idle funds/assets, thereby driving economic growth and economic equilibrium.